Project-Based Learning Students Worksheets on Students' Critical Thinking Skills and Independence in Social Studies Learning Courses - Yudiana, I Kadek Edi; Nirmayani, L. Heny; Sari, Ni Made Dainivitri Sinta (Thinking Skills and Creativity Journal, 2024)
Despite the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program for over two years, the critical thinking skills and independence of students in the learning process have not yet reached optimal levels. This study aims to investigate the impact of project-based learning (PjBL) student worksheets on critical thinking skills and student independence in social studies courses. The research employed a quasi-experimental design. The population comprised all fourth-semester elementary education students, totaling 256 students distributed evenly across nine classes. The sample consisted of fourth-semester PGSD students. Data collected included scores from critical thinking skills tests. Data analysis methods included descriptive analysis and inferential statistical analysis, specifically using MANOVA tests. The results indicated a significant difference between the group of students who engaged in learning with PjBL-based worksheets and the group that did not, in terms of critical thinking skills. The group using PjBL-based worksheets had a higher average critical thinking score, with a difference of 9.76 points. This finding suggests that PjBL approaches significantly encourage and enhance students' critical thinking skills. Additionally, the results showed that student independence was also higher in the group using PjBL-based worksheets, with a noted difference of 7.47 points. It is recommended to strengthen the implementation of PjBL worksheets in the curriculum or teaching strategies and provide training for educators to effectively integrate PjBL worksheets into their teaching.